Corporate Governance Quality and Capital Structure Decisions: Empirical Evidence from Canada - Lin, Dan; Lin, Lu (Advances in Social Sciences Research Journal, 2019)
This study examines the relationship between corporate governance quality and capital structure of firms listed on the S&P/TSX composite index between 2009 and 2012. Using an aggregate corporate governance index, this study finds support for the outcome hypothesis, which argues that capital structure is an “outcome” of corporate governance quality. Governance quality is found to be positively associated with firms’ leverage. Firms with lower governance quality have lower leverage as these firms’ managers do not like to have only little free cash flow leftover or have extra constraints imposed by debt financing. In contrast, firms with higher governance quality are more leveraged because these firms have lower agency costs and thus lower cost of debt financing. As a result, they can take on more debts. The empirical evidence from this study illuminates important links between governance quality and financing decisions of firms.